Identification of Sida rhombifolia from Its Related Plants Using Thin-Layer Chromatographic Analysis - Sefni Reza Yolanda; Maria Bintang; Nanik Siti Aminah; Muhamad Insanu; Abdul Rohman; Mohamad Rafi; Dewi Anggraini Septaningsih (Indonesian Journal of Chemistry, 2023)
Sida rhombifolia belongs to the Malvaceae family and is often used to treat gout in Indonesia. S. rhombifolia has many efficacies and contains many different chemical components. The abundance and variation of chemical content and chemical compounds in this medicinal plant are challenging factors in ensuring medicinal plants' safety and quality control. Thin-layer chromatography (TLC) fingerprint analysis derived from S. rhombifolia extract can also be used for the medicinal plant's quality control. This research aimed to develop the optimum condition for the chemical fingerprint analysis of S. rhombifolia using a TLC fingerprint analysis. A total of 11 bands were produced with optimum separation using silica gel 60 F254 TLC plate, a mixed mobile phase condition with chloroform, ethyl acetate, and methanol (6.5:2:1.5). This fingerprint analysis performed an excellent separation in the TLC plate at 366 nm with sulfuric acid as reagent derivatization. In general, the results of the analysis validation, including stability, specificity, precision, and robustness of TLC fingerprints, met the acceptance criteria. The TLC fingerprint of S. rhombifolia can be distinguished from 2 related plants with similar leaf shapes, Turnera ulmifolia L. and Hibiscus rosa-sinensis. The developed method was validated, so it could be used to control S. rhombifolia quality.